E-Learning Application Training for AL-SAFITRI Vocational School Teachers in South Buton Regency - Wiwi, Muhammad Hibrian; Awaluddin, Muhammad (Room of Civil Society Development, 2023)
Combining face-to-face meetings, in this case in class, with electronic learning can increase the contribution and interactivity between students. Through face-to-face students can get to know fellow students and their accompanying teachers. This familiarity greatly supports virtual collaborative work. Improving the quality of education at SMK 1 Al-Safitri is one of them by conducting online learning (in the network). E-Learning can be interpreted as a science of learning without having to use printed paper/hand out the material presented. On average, people working in the field of e-learning, especially from the fields of education, psychology, and computer science, know and use Moodle. teacher accounts that provide teaching topics or provide other subject matters besides being able to provide teaching topics there are several advantages of this Moodle LMS, namely there is a quiz feature, or videos.